364 A personal neoantigen vaccine NEO-PV-01 in combination with chemotherapy and pembrolizumab induces broad de novo immune responses in first line, non-squamous NSCLC. (10th December 2020) - Awad, Mark; Spigel, David; Garon, Edward; Waqar, Saiama; Lisberg, Aaron; Moles, Melissa; Tepper, Jennifer; Lamb, April; Wanamaker, Amy; Khondker, Zakaria; Srouji, John; Dong, Jesse; et al.
Abstract : Background: Neoantigens arising from mutations in cancer cell DNA are important targets for T cell mediated anti-tumor immunity. NEO-PV-01 is a personal neoantigen vaccine of up to 20 peptides (14–35 amino acids) based on a patient's HLA profile and bioinformatic analysis of tumor neoantigens. We report here clinical and immune data for NT-002, a Phase 1b study of NEO-PV-01 with pemetrexed, carboplatin, and pembrolizumab as first-line therapy for advanced non-squamous NSCLC. Methods: Patients received 12 weeks of pembrolizumab (Q3W) plus carboplatin and pemetrexed. NEO-PV-01 was then given subcutaneously in a prime-boost format spanning 12 weeks, followed by pembrolizumab for up to 2 years. The primary objective was safety; secondary objectives included overall response rate (ORR), clinical benefit rate (CBR), progression-free survival (PFS), and overall survival (OS). Comprehensive immune assessments were performed with peripheral blood mononuclear cells and biopsies collected at weeks 0, 12, and 24. Results: A total of 38 patients initiated study treatment (ITT population); 21 patients received at least 1 dose NEO-PV-01 (vaccinated group, VAX). The demographics included 61% women and 82% with a smoking history. The regimen was well tolerated consistent with the pembrolizumab plus pemetrexed/carboplatin safety profile, with transient low-grade injection site reactions present in VAX (29%). Treatment-related study discontinuations were rare (2/38). The ORR/CBR for the ITT and VAX were 37%/69% and 57%/95%, respectively. Median PFS was 7.2 months (95% CI: 5.6, 16.8) for both the ITT and VAX, and median OS 16.8 months (95% CI: 11.6, NR) for both groups. Interim immune analysis on 8 patients revealed neoantigen-specific CD4+ and CD8+ T cell responses against 48% of vaccine peptides. T cell responses were durable at 52 weeks and exhibited a memory phenotype with cytolytic potential. Epitope spread was observed in 3 of 5 patients analyzed thus far. Further, assessments of immune and molecular correlates of clinical response identified both tumor mutation burden and baseline levels of T cell infiltration in tumor as highly predictive of durable PFS (p= 0.005 and p= 7.2e-07 (for CD8), respectively). Additional correlates of clinical outcomes with molecular and immunologic responses will be presented. Conclusions: NEO-PV-01 in combination with pembrolizumab and carboplatin/pemetrexed is feasible, has a good safety profile, and induces de novo immune responses in first line non-squamous NSCLC. The association of baseline disease characteristics to prolonged PFS suggests future patient enrichment strategies for evaluation of this novel regimen in a phase 2 trial. Trial Registration: NCT03380871 Ethics Approval: The clinical study is conducted in accordance with ethical principles founded in the Declaration of Helsinki and approved by the local institutional review board and health authorities.